A community- based study of the prevalence and risk factor for “Schistosoma haematobium” in Two Endemic Districts of Taiz Governorate, Yemen - Al-Kabab, Abdullnasser Ahmed; El-Sheikh, Einas Ibrahim; Al-Mikhlafy, Abdulla Abdu (Journal of medical and pharmaceutical sciences, 2023)
Background: Schistosomiasis is still a major public health problem despite launching preventive chemotherapy campaigns (using Praziquantel) through yearly treatment of school-age children since 2008. Objective: To conclude: prevalence, contributing factors, intensity for Schistosoma Haematobium in Al-Shmaytin & Al-Mwaset districts-Taiz, Yemen. Methods: a cross-sectional study, data on age, sex, marital status, income, education, location, water contact, medical history (MH), urine test results (filtration method used to detect S. haematobium &concentration methods for the detection of infection intensities), were gathered using structured questionnaires between March & April 2021. Sample size calculated using appropriate formula. 298 individuals selected by systematic random sampling. Informed consent obtained. For statistical analysis, SPSS version 24 is used. For “p”-values, the statistical significance was set at 0.05. Results: S. haematobium was found in 17 of 273 respondents, with a prevalence of 6.2%, higher in Al-Shmaytin (9.2%) than in Al-Mwaset (3.5%), and a light-intensity 59%. Adjusted Odds Ratio (AOR) for the following variables (95% confidence interval (CI)): district 3.7 (12 cases from Al-Shmaytin 9.2%), age 1.0 (13 cases from 6-18 years 7.8%), sex 2.8 (13 cases from female 7.4%), marital 0.3 (15 cases from single 8%), educational status 1.3 (15 cases from Illiterate/Essential School 6%), swimming/bathing 2.0 (13 cases 8.6%), wear shoes 0.4 (15 cases from those who do not wear shoes 8.1%), urinate near water 1.7 (8 cases 9.8%), family member with disease 1.0 (5 cases 7.1%), dysuria 1.7 (8 cases 8.3%), and receiving anti-schistosomiasis drugs 0.9 (9 cases among those didn’t receiving drugs 7%). All had low monthly incomes and no sanitation. Prevalent among: secondary school and higher (2, 8.7%), unaware of schistosomiasis (15, 7.4%), and unaware of prophylaxis (16, 7.1%). Conclusions: Hypo-endemic urinary schistosomiasis in study areas. Most patients from Alsafiah, females, 6-18 years, light-intensity, swimming/bathing, single, didn’t receive Praziquantel®, urinated near water, had dysuria, didn’t wear shoes, had diseased family members, lacked sanitation, were unaware of schistosomiasis and its prevention, lived near water sources, and had low monthly income.